Facial nerve stimulation in adult cochlear implant recipients with far advanced otosclerosis. Issue 1 (29th November 2022) - Tuset, Maria‐Pia; Baptiste, Amandine; Cyna Gorse, Françoise; Sterkers, Olivier; Nguyen, Yann; Lahlou, Ghizlène; Ferrary, Evelyne; Mosnier, Isabelle
Abstract: Objectives: The objective of this study was to predict occurrence of facial nerve stimulation (FNS) in cochlear implanted patients for far‐advanced otosclerosis (FAO) by correlating preoperative computed tomography (CT)‐scan data to FNS and to evaluate FNS impact on hearing outcomes. Methods: Retrospective analysis on 91 ears (76 patients) implanted for FAO. Electrodes were straight (50%) or perimodiolar (50%). Demographic data, extension of otosclerosis on preoperative CT scan, occurrence of FNS, and speech performance were analyzed. Results: Prevalence of FNS was 21% (19 ears). FNS appeared during the first month (21%), 1–6 months (26%), 6–12 months (21%), and over 1 year (32%) postimplantation. Cumulative incidence of FNS at 15 years was 33% (95% CI = [14–47%]). Extension of otosclerotic lesions on preimplantation CT‐scan was more severe in FNS ears compared to No‐FNS ( p  < .05): for Stage III, 13/19 (68%) and 18/72 (25%) ears for FNS and No‐FNS groups, respectively ( p  < .05). Location of otosclerotic lesions relative to the facial nerve canal was similar whatever the presence or not of FNS. Electrode array had no impact on FNS occurrence. At 1 year post‐implantation, duration of profound hearing loss (≥5 years) and previous stapedotomy were negatively associated with speech performance. FNS did not impact hearing outcomes, despite a lower percentage of activated electrodes ( p  < .01) in the FNS group. Nevertheless, FNS were associated with a decrease of speech performance both in quiet ( p  < .001) and in noise ( p  < .05). Conclusion: Cochlear implanted patients for FAO are at greater risk of developing FNS affecting speech performance over time, probably due to a higher percentage of deactivated electrodes. High resolution CT‐scan is an essential tool allowing FNS prediction but not time of onset. Level of evidence: 2b, Laryngoscope Investigative Otolaryngology, 2022. Abstract : Prognostic factors for facial nerve stimulations on cochlear implanted patients for far advanced otosclerosis were studied. Radiological analysis using our classification allows prediction of stimulations. Short‐term hearing outcomes were not modified but long‐term hearing outcomes showed a tendency to decrease.